Dissemination of cognitive behavioral therapy for substance use disorders in the Department of Veterans Affairs Health Care System: Description and evaluation of Veteran outcomes. Issue 2 (3rd April 2021) - DeMarce, Josephine M.; Gnys, Maryann; Raffa, Susan D.; Kumpula, Mandy; Karlin, Bradley E.
Abstract: Background: As part of the nation's largest dissemination and implementation of evidence-based psychotherapies (EBPs) and the promotion of EBPs for substance use disorders (SUDs), the Veterans Health Administration (VHA) is working to nationally implement Cognitive Behavioral Therapy for SUD (CBT-SUD). The current manuscript describes the approach to system-wide training and reports Veteran outcomes associated with CBT-SUD implementation. Methods : Four-hundred fifty-eight Veterans with a range of treatment goals received treatment through the Department of Veterans Affairs (VA) CBT-SUD Training Program. Veteran outcomes related to substance use, substance use-related problems, and quality of life were assessed with the Brief Addiction Monitor, the Short Inventory of Problems, and the World Health Organization Quality of Life-BREF. Results: Statistically significant reductions in alcohol use, heavy alcohol use, other drug use, and substance use-related problems, as well as significant improvements in quality of life, were observed over the course of treatment. Conclusions: Program evaluation findings suggest that large-scale training in and implementation of EBPs for SUDs is associated with improvements in substance use and other functional outcomes. Limitations from this real-world implementation project, including the lack of a control group and missing post-treatment data, are discussed.